8 A retrospective review of a consecutive cohort of patients treated for infective endocarditis: a single centre study from beaumont hospital. (5th October 2017) - Buckley, A; Khan, H; Connor, CO; O'Brien, J; McAdam, BF
Abstract : Introduction: I nfective endocarditis (IE) is a life threatening infection associated with bacteraemia and the formation of valvular lesions. We aimed to characterise patients with a diagnosis of IE at our centre and assess their clinical features, bacteriology and outcomes. Methods: We retrospectively reviewed patient records of a consecutive cohort of patients who were treated for IE in Beaumont hospital from December 2011 to December 2016. Patients were treated based on clinical suspicion and Duke's scores. We identified patient demographics, predisposing risk factors, organisms (table 1), transoesophageal echo (TOE) features and outcomes. Results: During this 5-year period, 164 patients were treated for IE after TOE. As per Duke's score, there were 102 definite, 56 probable, 1 rejected and 5 had incomplete data. "Probable" IE were mostly culture-negative (53%). Mean age was 62 years, range 19–92 years and 64% were male. Staphylococcal (figure 1) were the most common species identified on blood culture (42%), of which, most were MSSA (27%) and only 7(4%) MRSA. 11% of cases were caused by Streptococcus organisms and 26% of cases were culture negative. A significant number of Staph cases were related to central venous catheters (CVCs) in situ (n=41), haemodialysis lines (n=28) and cardiac implantable electrical devices (CIEDs), n=27(16%). Right-sided disease was predominantly seen with Staph species (57%) with 25.9% of CIED infections subsequently requiring either box change or lead extraction. 10 cases were IVDU-related. There were 26(16%) cases of prosthetic valve endocarditis and these cases were prescribed more antibiotics on average (2.26 vs 1.74) but the mean duration of treatment was similar to native valve disease (6 weeks). A significant proportion of patients suffered embolic phenomena (table 2) (23%) and most of these were cerebral emboli with 4% having abscess formation requiring drainage. Total mortality rate was 14(8.5%) and the majority were Staph positive (64%). 10(6%) mortalities were directly due to IE and 4(2.4%) due to another cause. Only 6(4%) patients underwent valve repair and 5(3%) underwent valve replacement. 9(5.4%) had 2 presentations of IE with an average of 14 months between presentations. Staph Aureus was most frequently associated with repeat presentations and all such patients had risk factors for IE, with CIED and IVDU being the most frequent. Conclusions: We found a significant number of CIED and CVC related infections which contributed to the burden of IE in this cohort, primarily with MSSA organisms with a substantial requirement for device removal. In addition this organism was associated with more recurrent presentations and embolic events. A small number required cardiac surgery and our overall mortality rate is relatively low compared to international rates; this may be explained by a high index of clinical suspicion and aggressive early antimicrobial treatment.